1983
DOI: 10.1203/00006450-198309000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of the Human Placenta Perfused in Vitro: Glucose Transfer and Utilization, O2 Consumption, Lactate and Ammonia Production

Abstract: SummaryOxygen consumption, glucose transfer and utilization, and lactate and ammonia release were studied in the human full term placenta using an in vitro perfusion technique. DGlucose was the only substrate added to the perfusion fluid. On the maternal side, oxygen and glucose were taken up at a constant rate during perfusion. On the fetal side, a lower oxygen uptake was observed. Glucose was steadily released into the fetal perfusate as a result of the downhill concentration gradient established between mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2
2

Year Published

1986
1986
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(25 citation statements)
references
References 9 publications
2
19
2
2
Order By: Relevance
“…The HPLC results suggest that during the time of the experiment (1.5 h), the pool of glucose used for lactate production is independent of the glucose being transported from the maternal perfusate to the fetal effluent. This is consistent with previous research suggesting the lactate released may have been synthesised, at least in part, before perfusion [16,18].…”
Section: Discussionsupporting
confidence: 82%
“…The HPLC results suggest that during the time of the experiment (1.5 h), the pool of glucose used for lactate production is independent of the glucose being transported from the maternal perfusate to the fetal effluent. This is consistent with previous research suggesting the lactate released may have been synthesised, at least in part, before perfusion [16,18].…”
Section: Discussionsupporting
confidence: 82%
“…However it is of the same order of magnitude of values measured in the fetoplacental unit of the rabbit (23) and the cow (24). Although previous studies have shown that the conditions of oxygenation used in our perfusions are within the physiological range (14,25), we still should consider the possibility that the oxygen consumption had been physically limited in our experiments. In maternal physiological conditions (4 to 7 mM arterial glucose), the maximal proportion of glucose which is retained, but not metabolized, within the placenta is very small but increases dramatically during maternal hyperglycemia (Fig.…”
Section: Discussionmentioning
confidence: 71%
“…The present study establishes the relationships that exist between placental glucose uptake from the maternal circulation, transfer to the fetal circulation and utilization, and maternal glucose concentration. The rates of glucose uptake and transfer were proportional to maternal glucose concentration up to 17-22 mM for a maternofetal gradient of [14][15][16][17][18][19] mM. Above this value both glucose uptake and transfer rates appeared to be limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Five human placentas from uncomplicated pregnancies were collected immediately after cesarean sections. Perfusion of a suitable placental lobule was carried out as described previously (32). The placenta was washed before perfusion, and the medium was recirculated in the fetal and maternal circulation for 120 min.…”
Section: Methodsmentioning
confidence: 99%